Framework for Development and Evaluation of Community Engagement - Tim Haslett; Chris Ballenden; Louise Bassett; Saroj Godbole; Kelly Walker (International Journal for Court Administration, 2012)
This paper examines Australia's first Neighbourhood Justice Centre (NJC) which is based Melbourne and was established in 2007. It outlines the history of the centre and proposes a framework for its evaluation. The paper discusses three extant models for community engagement and identifies a common theme of development and evolution in both process and structure. The paper identifies and discusses five phases for the development and evolution of the NJC and relates these to existing models. The paper also discusses the shifting emphasis of resource allocation during this development process. The paper concludes by proposing a series of questions to evaluate the development of a Community.